Wood-Inhabiting Macrofungi Proposed for Conservation from the Primeval Bog of Bátorliget - Rimóczi Imre (ACTA SILVATICA ET LIGNARIA HUNGARICA: AN INTERNATIONAL JOURNAL IN FOREST, WOOD AND ENVIRONMENTAL SCIENCES, 2009)
MatarkaID=834212